Morphological and topological responses of roots to defoliation and nitrogen supply in Lolium perenne and Festuca ovina - Dawson, L A (The New phytologist, 2004)
•  This study examined morphological and topological responses of nodal root axes to defoliation in a fast- and a slow-growing grass species. •  Vegetative tillers of both Lolium perenne and Festuca ovina were grown on slant boards and either left intact or subjected to repeated defoliation, under both a high nitrogen (N) and a low N supply. Root length, diameter and branching characteristics were measured on individual nodal root axes. •  The total axis root length of F. ovina was less when plants had been defoliated. Root axis weight, primary root axis length and primary root diameter were also less with defoliation than an undefoliated control, under high N. Under low N conditions the root axes of F. ovina had a more randomly branched topology without defoliation. For L. perenne under low N conditions, the length of the primary root axis was longer with defoliation than in an undefoliated control, while the primary root axis diameter decreased. By contrast to F. ovina, the root axes of L. perenne had a more randomly branched topology without defoliation only when supplied with high N. •  The greatest plasticity in branching caused by defoliation was observed under high N for L. perenne and under low N for F. ovina. Although grass root axis topology has, in general, a herringbone in structure, the nodal root system can alter root axis structure in response to defoliation